What it's like to be a bird : from flying to nesting, eating to singing -- what birds are doing, and why - Sibley, David, 1961- (Alfred A. Knopf, 2020)
"Can birds smell?" "Is this the same cardinal that was at my feeder last year?" "Do robins 'hear' worms?" In "What It's Like to Be a Bird," David Sibley answers the most frequently asked questions about the birds we see most often. This special, large-format volume is geared as much to nonbirders as it is to the out-and-out obsessed, covering more than two hundred species and including more than 330 new illustrations by the author. While its focus is on familiar backyard birds--blue jays, nuthatches, chickadees--it also examines certain species that can be fairly easily observed, such as the seashore-dwelling Atlantic puffin. David Sibley's exacting artwork and wide-ranging expertise bring observed behaviors vividly to life. (For most species, the primary illustration is reproduced life-sized.) And while the text is aimed at adults--including fascinating new scientific research on the myriad ways birds have adapted to environmental changes--it is nontechnical, making it the perfect occasion for parents and grandparents to share their love of birds with young children, who will delight in the big, full-color illustrations of birds in action. Unlike any other book he has written, "What It's Like to Be a Bird" is poised to bring a whole new audience to David Sibley's world of birds." -- Amazon.com.